Monitoring Pilkada 2024 di Kecamatan Setiabudi Jakarta Selatan: Dinamika Lokal dan Hasil Akhir - Safitri, Anggita Ayu; Nugraha, Asma Adila; Fadillah, Tirta Nur (UIN Sunan Gunung Djati Bandung, 2025)
This study focuses on monitoring the 2024 regional elections (Pilkada) in Setiabudi District, South Jakarta, emphasizing local dynamics at TPS 19 and its implications for the democratic process. This study aims to examine the socio-political challenges, technical aspects, and election results in this urban district with diverse demographic composition. Using a qualitative approach and case study method, data were collected through in-depth interviews, direct observation, and document analysis, with thematic analysis applied to identify key findings. The results highlight significant issues, such as voter apathy, logistical challenges, and the role of independent oversight in improving election accountability. The study concludes that inclusive policies, increased transparency, and targeted socialization strategies are essential to increasing voter participation and trust. These findings provide valuable insights for policymakers and election organizers in optimizing election management and public engagement in urban environments. By implementing the recommendations from this study, it is hoped that the quality of democracy in Indonesia can be improved through increased voter participation, transparency, and more effective election management.